The framework electricity market in Peru - Okumura Suzuki, Pablo Arturo (2015)
Throughout the decade of 1990, Peru went through a process of liberalization and privatization, a process that was reflected on the mechanism of provision of utilities in the country.In the present article, the author studies the previously mentioned process focusing in the power sector, analyzing it from the Law on Electric Concessions reforms and focusing on its commercial function. He also offers a critical and descriptive overview, including the advantages and disadvantages of the Peruvian model.